Liquid Chromatography-Mass Spectrometry-Based Untargeted Metabolomics Analysis of Differential Metabolites in Three Types of Boza Made from Different Raw Materials - WANG Qi, GAO Yan, XUE Juanjuan, ZENG Jun, HUO Xiangdong, ZHAO Zhongkai (Shipin Kexue)
Untargeted metabolomics based on ultra-high performance liquid chromatography-quadrupole-time of flight-mass spectrometry (UPLC-Q-TOF-MS) was adopted to study three types of Boza, made from different raw materials. Multivariate statistical techniques such as principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA) were used to screening for differential metabolites, and pathway enrichment analysis of differential metabolites was carried out. The results showed that there were significant differences in metabolites among the three types of Boza. Altogether, 109, 124 and 114 differential metabolites were identified in intangible cultural heritage (G1) vs traditional Talmi Boza (G2), G1 vs traditional corn Boza (G3), and G3 vs G2, respectively. These differential metabolites mainly included lipids and lipid-like molecules, organic acids and their derivatives, organic heterocyclic compounds, phenylpropanoids, and polyketones. The difference might be caused by the difference in raw materials. According to Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathway enrichment analysis, these differential metabolites mainly participated in the biosynthesis of various secondary metabolites in plants, the biosynthesis of phenylpropanoids, the biosynthesis and degradation of flavonoids, and other metabolic pathways. This study provides a theoretical basis for the comprehensive development and utilization of Boza.